Aspek Religius dalam Antologi Puisi 99 Untuk Tuhanku Karya Emha Ainun Nadjib: Kajian Sosiologi Sastra dan Implementasinya Sebagai Bahan Ajar Sastra di SMA Negeri 1 Suruh - Rahmanto, Yusuf Candra Tri, Drs. Adyana Sunanda, M.Pd (2017)
The purpose of this study was to describe: 1) how to structure that builds the poetry anthology 99 Untuk Tuhanku by Emha Ainun Nadjib's work, 2) how the religious aspect contained in the poetry anthology 99 Untuk Tuhanku by Emha Ainun Nadjib's work, 3) how the implementation of the research results anthology of poetry 99 Untuk Tuhanku by Emha Ainun Nadjib's work. This research uses descriptive qualitative research method. The research data in the form of words in the array or line, and poetry are to be found in poetry antalogi 99 Untuk Tuhanku by Emha Ainun Nadjib's work, as well as information from teachers about the implementation of Indonesian literature teaching materials. Source of data in this study is a book of poetry antalogi 99 Untuk Tuhanku by Emha Ainun Nadjib's work, which taking techniques with engineering data sempling purposive (aim). Data collection techniques used engineering literature, see, notes and interviews. Data analysis techniques used model of semiotic reading techniques include heuristic and hermeneutic reading and Miles and Huberman's model. The themes contained in the poetry of the relationship between man and God. Feeling and tone represents, regret, longing, and emotion. Diction in the title of the poet chose to use numeralia represent the number of the most Beautiful, words that conveyed meaning implied. Pengimajian that dominates namely auditory imagery (vision). take into concrete poet's words, so the reader as if to see, hear, feel what it described poet. Language will find more to the connotative meaning. Broadly speaking, the mandate of which was delivered that always ask guidance from Allah SWT. 99 Untuk Tuhanku poetry anthologies by Emha Ainun Nadjib's work load four religious aspects, namely: 1) belief in supernatural powers, 2) a belief system, 3) the emotional response of humans, 4) understand their holy (sacred) and the sacred. Based on the results of research anthology 99 Untuk Tuhanku by Emha Ainun Nadjib's work can be implemented on a class X semester of 1 (one) in the High School 1 Suruh Competency Standards 5.